2022
DOI: 10.1186/s13613-022-01048-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different clinical risk scores to predict long-term survival and neurological outcome in adults after cardiac arrest: results from a prospective cohort study

Abstract: Background Several scoring systems have been used to predict short-term outcome in patients with out-of-hospital cardiac arrest (OHCA), including the disease-specific OHCA and CAHP (Cardiac Arrest Hospital Prognosis) scores, as well as the general severity-of-illness scores Acute Physiology and Chronic Health Evaluation II (APACHE II) and Simplified Acute Physiology Score II (SAPS II). This study aimed to assess the prognostic performance of these four scores to predict long-term outcomes (≥ 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Second, it was explicitly developed for use in IHCA and OHCA patients. Thus, it can be applied to unselected cardiac arrest patients, whereas the OHCA and CAHP score were developed for OHCA patients only and consequentially showed significantly worse performance when applied to IHCA patients in the subgroup analysis—a finding which is in line with previous publications [ 16 , 39 ]. The PROLOGUE score thus might be a promising alternative to the OHCA and CAHP scores mainly due to its better clinical applicability by omitting the no-flow time as a parameter and broader suitability to OHCA and IHCA survivors with—in our study—similar prognostic accuracy.…”
Section: Discussionsupporting
confidence: 84%
“…Second, it was explicitly developed for use in IHCA and OHCA patients. Thus, it can be applied to unselected cardiac arrest patients, whereas the OHCA and CAHP score were developed for OHCA patients only and consequentially showed significantly worse performance when applied to IHCA patients in the subgroup analysis—a finding which is in line with previous publications [ 16 , 39 ]. The PROLOGUE score thus might be a promising alternative to the OHCA and CAHP scores mainly due to its better clinical applicability by omitting the no-flow time as a parameter and broader suitability to OHCA and IHCA survivors with—in our study—similar prognostic accuracy.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, Blatter et al . [ 29 ], observing 415 patients, found that the AUROCs of OHCA, CAHP, APACHE II, and SAPS II scores had similar performances in predicting poor neurological outcomes at 2 years after cardiac arrest. Note that “general ICU scores,” such as APACHE II and SAPS II, could only be determined after 24 h, a limitation of their utility in the early phase of evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The study aimed to identify risk factors and prognostic markers for neurological outcomes after cardiac arrest with a maximum follow-up of 24 months. Details of the study’s conduct and procedures have been published previously 4 , 26 33 . Patients were treated in accordance with the local treatment protocol, which followed the respective recommendations from the European Resuscitation Council 34 36 .…”
Section: Methodsmentioning
confidence: 99%